2015
DOI: 10.1016/j.leukres.2015.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Novel CT domain-encoding splice forms of CTGF/CCN2 are expressed in B-lineage acute lymphoblastic leukaemia

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…The CTGF gene (6q23.2) is a relatively short gene composed of 5 exons that code for a 349-amino acid protein. A novel splice variant of CTGF encoding the C-terminal domain has been identified in the pediatric precursor B cell acute lymphoblastic l e u k e m i a w h i c h m a y b e i n v o l v e d w i t h tumorigenesis [5].…”
mentioning
confidence: 99%
“…The CTGF gene (6q23.2) is a relatively short gene composed of 5 exons that code for a 349-amino acid protein. A novel splice variant of CTGF encoding the C-terminal domain has been identified in the pediatric precursor B cell acute lymphoblastic l e u k e m i a w h i c h m a y b e i n v o l v e d w i t h tumorigenesis [5].…”
mentioning
confidence: 99%
“…The N-terminal domain (modules I and II) has been shown to mediate differentiation and collagen synthesis, and the C-terminal domain (modules III and IV) has been shown to regulate cell proliferation (Gao and Brigstock 2004 ; Hall-Glenn and Lyons 2011 ). A recently study showed that C-terminal domain of CTGF was associated with cell proliferation in leukaemia (Welch et al 2015 ). It has been reported that the C-terminal domain of CTGF could stimulate cellular adhesion via the αv-β3 receptor (Ball et al 2003 ; Hoshijima et al 2006 ) and was involved in the fibrosis process (Rodrigues-Diez et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…CCN2 is mainly secreted as an extracellular protein and has been identified in various human biological fluids (Bradham et al 1991;Yang et al 1998). Loss of its 2 kDa N-terminal secretory signal peptide leads to intracellular retention of the protein (Welch et al 2015).…”
Section: Ccn2 Proteinmentioning
confidence: 99%
“…B‐ALL cells can also secrete CCN2 (Boag et al 2007; Welch et al 2015; Wells et al 2016), and addition of rhCCN2 promotes adhesion of B‐ALL cells to stromal cells in vitro, which induces them to overexpress genes associated with cell cycle, intracellular transport and ECM synthesis (Wells et al 2016). Therefore, CCN2 secreted by B‐ALL cells might also enhance leukemia engraftment due to its modifying effects on the microenvironment and ECM interactions (Wells et al 2016).…”
Section: Ccn2 and Malignant Hematopoiesismentioning
confidence: 99%
See 1 more Smart Citation